2013
DOI: 10.1007/s00787-013-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Marked elevation of adrenal steroids, especially androgens, in saliva of prepubertal autistic children

Abstract: Autism is diagnosed on the basis of behavioral manifestations, but its biomarkers are not well defined. A strong gender bias typifying autism (it is 4–5 times more prevalent in males) suggests involvement of steroid hormones in autism pathobiology. In order to evaluate the potential roles of such hormones in autism, we compared the salivary levels of 22 steroids in prepubertal autistic male and female children from two age groups (3–4 and 7–9 years old) with those in healthy controls. The steroids were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 54 publications
3
70
1
Order By: Relevance
“…Peripherally, glutamate was found to affect taste sensation, skin pain sensation, and pancreatic exocrine function (15). The rise in serum glutamic acid was in part attributed to the failure of its conversion to glutamine due to vitamin B6 deficiency in such patients (15), in addition to the modulatory effect of neuroactive steroids on glutamate level (11). Such findings of high glutamate led some researchers to consider glutamate as a diagnostic tool for early detection of autism (26).…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally, glutamate was found to affect taste sensation, skin pain sensation, and pancreatic exocrine function (15). The rise in serum glutamic acid was in part attributed to the failure of its conversion to glutamine due to vitamin B6 deficiency in such patients (15), in addition to the modulatory effect of neuroactive steroids on glutamate level (11). Such findings of high glutamate led some researchers to consider glutamate as a diagnostic tool for early detection of autism (26).…”
Section: Discussionmentioning
confidence: 99%
“…There should be reduced emotional changes compared to collecting blood samples and thus possibly increased accuracy of results [121]. Saliva samples have proved appropriate in the past for determining levels of several neuroactive and related steroids [72,[122][123][124][125][126].…”
Section: Discussionmentioning
confidence: 99%
“…This is further evidence of dysregulation and is referred to as the absence of the typical sexual dimorphism. Majewska et al [72] found that saliva androstenedione levels in ASD subjects are no different in a 7-9 year old group or a 3-4 year old group and HCs. Tordjman et al…”
Section: Androstenedionementioning
confidence: 98%
See 2 more Smart Citations